METHODOLOGICAL GUIDELINES FOR APPLICATION OF IMMUNOMODULATORY AGENTS IN COMBINATION THERAPY OF HELMINTHOSIS - O. I. Mamykova (Российский паразитологический журнал, 2016)
Methodological guidelines for application of immunomodulatory agents in combination therapy of helminthosis have been developed. The list of immunomodulatory drugs recommended for combination therapy of animal helminthosis includes T-activin, Ribotan, Ronkoleikin, Polyoxidonium. The isolated drug application reveals the selective mechanism of their immune-biological effects. T-activin directly affects the cellular immune response in primary and secondary disorders of immune system and in drug-induced immunodeficiency diseases. Ribotan stimulates production of antibodies against specific antigens as well as interferon and lymphokines synthesis. Ribotan has a bioregulatory activity influencing the functional status of the liver monooxygenase system. Biological effects of Ronkoleikin are directed at growth, definition and activation of T- and B-lymphocytes, synthesis of different isotypes of immunoglobulins in plasma cells, production of interferons α, β, γ. Pilot injections of Polyoxidonium prevent negative effects of the anthelmintic drug on the functional activity of T- and B-lymphocytes and stabilize the immune system.